ROLE OF INFORMATION TECHNOLOGY IN EDUCATION SECTOR: SCRUTINIZING ITS MERITS AND DEVELOPMENTS - Raju, Valliappan (MATTER: International Journal of Science and Technology, 2016)
It’s known that technology has invaded all industries and for almost all services. This article will concentrate more on the merits of technology in Education sector and highlights its crucial prominence to its fraternity. Many institutions have adopted IT inside their campus and reaping their fruit however on bird’s view there may be few left-outs who are still demanding authenticity. There are needs to still extend the service in the Education sector, for instance, Online Education has become a global hit but still, many students do not conceive it as a professional model of education. Only leading Institutions like Oxford and Harvard are gaining advantages by these innovations. Author has taken efforts to collect all relevant information’s and put in simple & readable format herewith. Justifications are provided wherever necessary. Implementing appropriate technology is under the discretion of the institution and their requirement. This report does not campaign or propaganda any particular technology system or software that needs to be adopted. Evaluating the vox-pop outputs from Institutions, IT Enabled Service companies and fraternity of the institutions, the research was done.